Molecular dynamics simulation on the friction properties of confined nanofluids. (March 2023) - Xu, Cang; Schall, David; Barber, Gary
Abstract: The determination of physical properties of nanofluids is mature, but the knowledge of tribological properties of nanofluids across a broad range of lubrication regimes is limited. In this paper, the effects of surface roughness, fluid thickness, nanoparticle hardness, and number of nanoparticles on friction are explored systematical using a 2D Lennard-Jones molecular dynamics model. LJ parameters were chosen such that the ratio of stiffness of the nanoparticles to the opposing surfaces was approximately equal to ratio of stiffness of either aluminum oxide or zinc oxide to steel. A total of two hundred and twenty configurations were investigated. The results show that the benefits or drawbacks of nanofluid lubricants are sensitive to the friction regime (boundary, mixed, or hydrodynamic). When nanoparticles are present in lubricant-starved boundary conditions (fluid thickness less than the surface roughness amplitude), nanoparticles offer support that keeps the opposing surfaces separated. This separation results in reduced contact between the opposing surfaces and provides surface smoothing, which in turn lowers friction about 15.8–96.75 % relative to the base fluid. At intermediate levels of fluid thickness where the fluid thickness and roughness are approximately equal, the presence of nanoparticles has a detrimental effect on friction. Nanoparticles jam and lock surfaces together and increase friction about 2.63–1100 % relative to the base fluid. As fluid thickness increases, the friction of the nanofluid generally remains higher than the base fluid likely due to the increased viscosity of fluid due to the presence of the nanoparticles. This work suggests nanofluids may offer limited benefits under specific lubrication conditions but are detrimental under most conditions. Graphical Abstract: Figure 11 shows the percentage friction increase (or decrease) for each type of nanofluid relative to the base fluid as a function of fluid thickness and roughness by replot the average friction force data shown in Figures 4 and 8. For the LR surface, single nanoparticles have a beneficial effect on friction at fluid thicknesses > 10σ, offering approximately a 75 % reduction in friction, which is due to plastic deformation and smoothing of the surface asperities suggested by the inspection of the atomic trajectories shown in Figures 6 and 7. ga1